Evaluation of Biofilm Formation on Different Orthodontic Bracket Materials. (Bangladesh Journal of Medical Science, 2025)
Background Biofilm formation on orthodontic brackets is a significant concern due to its implications on oral hygiene, caries development, and periodontal health. The choice of bracket material may influence biofilm adherence and growth. This study evaluates biofilm formation on different orthodontic bracket materials to identify the least biofilm-retentive options. Materials and Methods A total of 60 orthodontic brackets, divided into three groups based on material type—metallic (n=20), ceramic (n=20), and composite resin (n=20)—were tested. Artificial saliva was used to mimic oral conditions, and Streptococcus mutans was selected as the primary biofilm-forming bacterium. Brackets were incubated for 48 hours at 37°C, after which biofilm quantification was performed using crystal violet staining and spectrophotometric analysis at 595 nm. Statistical analysis was conducted using ANOVA to compare biofilm formation across groups. Results The mean optical density (OD) values for biofilm formation were as follows: metallic brackets (0.25 ± 0.05), ceramic brackets (0.42 ± 0.08), and composite resin brackets (0.58 ± 0.07). Metallic brackets demonstrated the lowest biofilm formation, which was statistically significant compared to ceramic and composite resin brackets (p < 0.05). Ceramic brackets showed moderate biofilm formation, while composite resin brackets exhibited the highest levels of biofilm accumulation. Conclusion Metallic brackets are less conducive to biofilm formation compared to ceramic and composite resin brackets, making them a preferable choice for minimizing biofilm-related complications during orthodontic treatment. These findings emphasize the importance of material selection in orthodontic practice to promote better oral health outcomes.BJMS, Volume: 24. Supplementary Issue 2025, Page : 69-72